Cultured Human Retinal Pigment Epithelial (hRPE) Sheets: A Search for Suitable Storage Conditions. (11th April 2018) - Khan, Ayyad Z.; Utheim, Tor P.; Reppe, Sjur; Sandvik, Leiv; Lyberg, Torstein; Roald, Borghild B.-H.; Ibrahim, Ibrahim B.; Eidet, Jon R.
Abstract: The advancement of human retinal pigment epithelial cell (hRPE) replacement therapy is partly dependent on optimization of cell culture, cell preservation, and storage medium. This study was undertaken to search for a suitable storage temperature and storage medium for hRPE. hRPE monolayer sheets were cultured under standard conditions at 37°C and then randomized for storage at six temperatures (4, 16, 20, 24, 28, and 37°C) for 7 days. After revealing a suitable storage temperature, hRPE sheets were subsequently stored with and without the silk protein sericin added to the storage medium. Live/dead assay, light microscopy, pH, and phenotypic expression of various proteins were used to assess cell cultures stored at different temperatures. After 7 days of storage, hRPE morphology was best preserved at 4°C. Addition of sericin to the storage medium maintained the characteristic morphology of the preserved cells, and improved pigmentation and levels of pigmentation-related proteins in the cultured hRPE sheets following a 7-day storage period at 4°C.